Capacity Building of the Purworejo Regency Health Centre (BLUD) in the Preparation of Strategic and Business Plan Documents - Yeni Priatna Sari; Hetika Hetika; Andri Widianto; Yussri Sawani (Wikrama Parahita : Jurnal Pengabdian Masyarakat, 2026)
As Puskesmas transition into BLUD entities, they are required to develop structured medium-term planning documents that are both administratively sound and accountable. This community service activity aims to enhance the managerial and technical capacity of BLUD (Public Service Agency) Puskesmas in Purworejo Regency in preparing Strategic and Business Planning documents in accordance with regulations and healthcare service needs. This activity was conducted through workshops and intensive assistance by a team of lecturers from the D3 Accounting Program of Politeknik Harapan Bersama and the D4 Tax Accounting Program of Diponegoro University and Universiti Teknologi Mara, Malaysia, in collaboration with Wahyu Yeni Novi Public Accounting Firm. There are about 28 participants from 14 BLUD in Purworejo. The implementation method included module delivery, case studies, practical document preparation, and evaluation of participants' achievements. The results indicated an improvement in participants' understanding of the concepts and structure of Strategic and Business Planning documents, as well as their technical ability to tailor these documents to the specific characteristics of their respective Puskesmas. It showed that all the BLUDs were able to fulfil the template module for their strategic and business plans.   This intervention model, combining multi-institutional academic collaboration with professional practitioners, proved effective in overcoming common implementation gaps in public sector financial management reforms at the local level.